2006
DOI: 10.1021/ja063250+
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Thermodynamic and Kinetic Aspects of Oxidative Addition of PhE−EPh (E = S, Se, Te) to Mo(CO)3(PR3)2, W(CO)3(PR3)2, and Mo(N[tBu]Ar)3 Complexes. The Role of Oxidation State and Ancillary Ligands in Metal Complex Induced Chalcogenyl Radical Generation

Abstract: Enthalpies of oxidative addition of PhE-EPh (E = S, Se, Te) to the M(0) complexes M(PiPr3)2(CO)3 (M = Mo, W) to form stable complexes M(*EPh)(PiPr3)2(CO)3 are reported and compared to analogous data for addition to the Mo(III) complexes Mo(N[tBu]Ar)3 (Ar = 3,5-C6H3Me2) to form diamagnetic Mo(IV) phenyl chalcogenide complexes Mo(N[tBu]Ar)3(EPh). Reactions are increasingly exothermic based on metal complex, Mo(PiPr3)2(CO)3 < W(PiPr3)2(CO)3 < Mo(N[tBu]Ar)3, and in terms of chalcogenide, PhTe-TePh < PhSe-SePh < Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The temperature required to initiate productive homolytic cleavage of the Si–H bond is typically in the range of 150–200 °C, as shown through numerous studies on hydrosilylation of alkenes and alkynes on silicon surfaces. ,, Similarly, heating to 80 °C does not induce Si–EC bond formation, as shown by the control experiment with only heat ( vide supra ); heating to 80 °C appears to only serve to liquefy the chalcogenide molecules to form an even layer on the silicon surface. The 254 nm UV light, however, is of sufficient energy (112.6 kcal/mol) to induce cleavage of both the diaryl/dialkyl dichalcogenide E–E bond and the Si–H bond. Because of the high absorption coefficients at 254 nm for the three diphenyl dichalcogenides as well as the di- n -octadecyl disulfide (Figure S5, and corresponding calculations in Supporting Information), essentially all of the incident UV light would be absorbed by this molecular layer, and no UV light would directly impinge upon the silicon surface. The role of the 254 nm UV light, then, must be to cleave S–S, Se–Se, or Te–Te bonds (bond energies of 53–57, 40, and 30–35 kcal/mol, respectively) ,, at the surface of the melted REER layer, in close proximity to the quartz coverslip, to yield thiyl, selenyl, or telluryl radicals, RE• (E = S, Se, and Te), respectively, as outlined in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature required to initiate productive homolytic cleavage of the Si–H bond is typically in the range of 150–200 °C, as shown through numerous studies on hydrosilylation of alkenes and alkynes on silicon surfaces. ,, Similarly, heating to 80 °C does not induce Si–EC bond formation, as shown by the control experiment with only heat ( vide supra ); heating to 80 °C appears to only serve to liquefy the chalcogenide molecules to form an even layer on the silicon surface. The 254 nm UV light, however, is of sufficient energy (112.6 kcal/mol) to induce cleavage of both the diaryl/dialkyl dichalcogenide E–E bond and the Si–H bond. Because of the high absorption coefficients at 254 nm for the three diphenyl dichalcogenides as well as the di- n -octadecyl disulfide (Figure S5, and corresponding calculations in Supporting Information), essentially all of the incident UV light would be absorbed by this molecular layer, and no UV light would directly impinge upon the silicon surface. The role of the 254 nm UV light, then, must be to cleave S–S, Se–Se, or Te–Te bonds (bond energies of 53–57, 40, and 30–35 kcal/mol, respectively) ,, at the surface of the melted REER layer, in close proximity to the quartz coverslip, to yield thiyl, selenyl, or telluryl radicals, RE• (E = S, Se, and Te), respectively, as outlined in Figure .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The 254 nm UV light, however, is of sufficient energy (112.6 kcal/mol) to induce cleavage of both the diaryl/dialkyl dichalcogenide E–E bond and the Si–H bond. Because of the high absorption coefficients at 254 nm for the three diphenyl dichalcogenides as well as the di- n -octadecyl disulfide (Figure S5, and corresponding calculations in Supporting Information), essentially all of the incident UV light would be absorbed by this molecular layer, and no UV light would directly impinge upon the silicon surface. The role of the 254 nm UV light, then, must be to cleave S–S, Se–Se, or Te–Te bonds (bond energies of 53–57, 40, and 30–35 kcal/mol, respectively) ,, at the surface of the melted REER layer, in close proximity to the quartz coverslip, to yield thiyl, selenyl, or telluryl radicals, RE• (E = S, Se, and Te), respectively, as outlined in Figure . Diffusion of these radicals throughout the layer could then lead to formation of silyl radicals, Si•, at the surface, through removal of H• from surface-bound Si–H groups (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Consideration of the literature indicates that for many systems involving bonds to sulfur and selenium, e.g. E–H,6d E–C6d, E–P,47 and E–transition metal48,49,50 (E = S, Se), the bond to sulfur is generally the stronger; however, there are situations in which the reverse is observed. For example, the opposite trend has been observed for coordination of thio- and selenoethers to transition metals 51.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, comparison of the data in Table indicates that the Hg−SePh bond is slightly stronger than the Hg−SPh bond, whereas the Zn−SePh bond is slightly weaker than the Zn−SPh bond. Consideration of the literature indicates that, for many systems involving bonds to sulfur and selenium, e.g., E−H, E−C, E−P, and E−transition metal (E = S, Se), the bond to sulfur is generally the stronger; however, there are situations in which the reverse is observed. For example, the opposite trend has been observed for coordination of thio- and selenoethers to transition metals .…”
Section: Resultsmentioning
confidence: 99%
“…Neale and co-workers have shown that cleavage of Si–SiH 3 groups on hydride-terminated silicon nanoparticles may be the dominant initiation step for hydrosilyation with alkenes. The third route to formation of Si· is removal of the silicon-bound H· by a chalcogenyl radical, shown in Scheme c. ,, The thiyl, selenyl, and telluryl radicals would result from homolysis of the weak S–S, Se–Se, or Te–Te bond, which have bond dissociation energies of 53–57, ∼40, and ∼30–35 kcal/mol, respectively, under these high-temperature conditions (Scheme d) . Thiyl and selenyl radicals are known radical propagators, and presumably telluryl radicals would play a similar role, plucking hydrogen atoms from the silicon surface to produce silyl surface radicals, particularly under high concentrations of reagents. …”
Section: Resultsmentioning
confidence: 99%